Combining ability for yield and yield-associated traits in wheat (Triticum aestivum L.) - Afsar Ahmad1 and Rajesh Kumar Gupta2 (Electronic Journal of Plant Breeding, 2024)
The current breeding effort aims to develop new wheat genotypes with higher genetic potential, thereby contributing to food security. Ten wheat genotypes were crossed in a half-diallel mating design. The F1 progeny from the 45 crosses, along with their ten parents, were evaluated in a randomized block design to estimate combining ability and the nature of gene action. Analysis of variance for combining ability revealed significant mean squares for both general and specific combining abilities across all studied traits. This indicates the importance of both additive and non-additive gene effects in the inheritance of these traits. The GCA/SCA ratio suggested the predominance of non-additive genetic action for all studied traits. Only five parents (HD3086, UP 2748, WH 1105, UP 2565, and HD 2967) exhibited good general combining ability for yield and associated traits. However, but none of them were found good combiners for all traits. Twenty-one crosses exhibited significant specific combining ability for yield and associated traits. The crosses UP 2748 x HD 3059, UP2565 x HD3086, WH 1105 x UP 2526, WH 1105 x WH 1021, and HD 2967 x WH 1021 were identified as good specific combiners for higher grain yield and associated traits. Utilizing these crosses in breeding programs that exploit heterosis can lead to the creation of new wheat genotypes with a broader genetic base. This approach, which involves crossing high-performing parents for some traits with low-performing parents for others, has the potential to produce offspring with superior characteristics in the next generation due to interactions between dominant genes.